E-Dictionary of Basic Baris Dance Movements Based on SIBI Sign Language in SBdP Subjects for Deaf Students - Satria Ari Jaya, I Made; Anak Agung Gede Agung; I Wayan Sujana (Universitas Pendidikan Ganesha, 2024)
The lack of optimal Balinese dance skills, especially Baris dance for deaf students, causes them not to be able to show their existence. This is due to the lack of learning media that is in accordance with the learning style of deaf students, namely visual. Learning media that suits the learning style of deaf students is the E-Dictionary of Basic Movements of Baris Dance based on SIBI sign language. The purpose of this research is to develop learning media for the E-Dictionary of Basic Dance Movements based on SIBI sign language. The type of research conducted is development research with the ADDIE model with the subjects involved, namely learning content experts, instructional design experts, learning media experts, and 6 deaf students in grade VI. The data in this study were collected using non-test methods in the form of observation, interviews, questionnaires and performance assessments. Data analysis techniques used are descriptive qualitative, descriptive quantitative, and inferential statistics. The results of this study are in the form of effective E-Dictionary media for Basic Dance Movements, with the acquisition of validation results of design experts by 95%, content experts by 93.33%, instructional design experts by 95%, learning media experts by 95%, individual trials by 94.44%, small group trials by 93.40% which are qualified as very good. Based on the dependent sample t test, tcount = 7.233 was obtained. These results show tcount= 7.233 > ttable = 2.571. Basic Baris Dance Movement E-Dictionary media is effective in SBdP learning for deaf students.